LOX gene polymorphisms are associated with osteoporotic vertebral compression fracture in postmenopausal Chinese women - Xiao, Wenjin; He, Jinwei; Fu, Wenzhen; Xu, Youjia; Zhang, Zhenlin (Gene, 2020)
•To explore the effect of LOX gene polymorphisms on osteoporotic fractures susceptibility.•Genetic polymorphisms in LOX may contribute to susceptibility to OVCF.•The results could help identify women at higher risk of osteoporosis. Collagen cross-linking, which is regulated by lysyl oxidase (LOX), plays critical roles in bone mechanical strength. LOX can influence bone remodeling by modulating osteoblast and osteoclast activity. This study aimed to explore the effect of LOX gene polymorphisms on osteoporotic fractures susceptibility in postmenopausal Chinese women. This was a prospective study of postmenopausal women who visited the outpatient and community clinics of the local Hospital. Five tagging single nucleotide polymorphisms (SNPs) in the LOX gene were determined. Bone mineral density (BMD) was measured at the lumbar spine, femoral neck, and hip using dual-energy X-ray absorptiometry. Fractures were confirmed by X-ray and divided into: vertebral compression fracture (OVCF) and non-OVCF (all other fractures). This study included 602 patients with non-traumatic fractures and 1343 healthy volunteers. The rs1800449 was significantly associated with vertebral compression fracture (OVCF) after adjusting for age and BMI (P = 0.012). Compared with subjects with the GG genotype, the risk of having OVCF was 1.28 and 1.74, respectively for subjects with the GA and AA genotypes (P = 0.043 and P = 0.018). A recessive genetic model showed that carriers of the AA genotype had higher fracture risk compared to G carriers (GA and GG genotypes) (P = 0.015). The rs2288393 SNP exhibited marginally significant association with OVCF (P = 0.051). Haplotype analyses corroborated our single SNP results: both haplotype CGA and CCG contained rs10519694, rs2288393, and rs1800449, and were significant associated with OVCF (P = 0.048 and P = 0.032, respectively). On the other hand, we found no evidence of an association of LOX gene allelic variants with either BMD or non-OVCF (all P > 0.05). The results suggest that genetic polymorphisms in LOX may contribute to susceptibility to OVCF in Chinese postmenopausal women.